Práticas pedagógicas inovadoras: as lutas como conteúdo da educação física no ensino médio - Carmem Elisa Henn Brandl; Cristiane Boelhouwer; Kymberli Nadine Guios (Universidade Estadual do Oeste do Paraná, 2018)
Based on the assumption that the Fights are poorly developed in physical education classes, although they are part of the body culture, and so the contents that must be taught in the school, this research aimed to evaluate a pedagogical proposal of this content, based on pedagogy history- critical, comparing students' initial and final knowledge. The research was characterized as qualitative descriptive. A high school class and a physical education teacher from a State School of Paraná participated in the research. The data was collected through a questionnaire and through a field diary. The procedure consisted of study groups, elaboration of didactic material, pedagogical intervention and data collection. The results showed that while students are aware of different types of fights, the concept is limited and often misleading, especially relating it to violence. On the pedagogical practice, when comparing the previous knowledge with the knowledge demonstrated after the classes carried out, having as reference the proposed objectives, one can verify an evolution in both the conceptual dimension and in the attitudinal and procedural dimensions. It was concluded that from innovative and systematized pedagogical practices there is great possibility of introducing the content fights in the classes of Physical Education.